The Effect of Perceived Price, Location and Product Quality at Purimas Residence Purchase Decisions Batam Centre - Syahrizal, Rizki; Auzar, Silvia Revana (Universitas Batam, 2022)
In the midst of Indonesia's economic downturn during the pandemic, people tend to prioritize economic stability by minimizing spending on luxury goods. However, the reality is that there is an increase in buying and selling which affects the occupancy rate which is quite significant at Purimas Batam Center Residence. This study aims to analyze whether the perceived price, location, and product quality variables have an influence on purchasing decisions at Purimas Residence Batam Centre. This study uses quantitative techniques by collecting data through online questionnaires. The objects in this study used are residents who inhabit both as owners and or tenants at Purimas Residence Batam Centre. The total population in this study were 190 people. With a simple random sample technique, the sample obtained by the slovin formula is 129 respondents. This research uses multiple regression analysis with SPSS program. The results of this study indicate that; 1) Perceived price has a significant positive effect on purchasing decisions at Purimas Residence Batam Centre, 2) location has a significant positive effect on purchasing decisions at Purimas Residence Batam Centre, 3) Product quality has a significant positive effect on purchasing decisions at Purimas Residence Batam Centre, 4) Perveived Price, Location, and Product Quality have a significant positive effect simultaneous and significant impact on purchasing decisions with the object of research on of the Purimas Residence Batam Centre.